Factors affecting investors’ intention to invest in a peer-to peer lending platform in Malaysia: an extended technology acceptance model - Mohd Thas Thaker, Mohamed Asmy; Mohd Thas Thaker, Hassanudin; Rahman, Maya Puspa; Amin, Md Fouad; Allah Pitchay, Anwar; Oladokun, Nafiu Olaniyi (2019)
There has been significant growth in peer-to-peer (P2P) lending platforms in recent years, given the advancement of information and online technologies. Because this type of platform is gaining in importance and popularity, it becomes necessary to examine the factors that influence the behavioral intention of investors to invest in a P2P lending platform. Based on an extended technology acceptance model and using a structured survey questionnaire, this study examines the factors that influence retail investors to invest in a P2P lending platform in Klang Valley, Malaysia. The results show that intention to invest is mainly influenced or driven by trust. Other variables, namely perceived risk, perceived ease of use, and security, are found to have no impact on investors’ decisions. The study findings provide managerial implications and theoretical contributions.